PENERAPAN PENDEKATAN KONTRUTIFISME UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA KELAS VIII SMP NEGARI 4 KOTABARU - Sri Juniati (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2015)
This research is a class act (Action research) which aims to determine the effectiveness of the students received materials to write a poem with the adoption of a constructivist approach by teachers in the classroom. This study is based on a constructivist approach. The mechanism of the implementation done in two cycles. Each cycle consists of three stages, namely: (1) planning, (2) action, (3) the stage of reflection. This research data is the test data and behavioral data. Data were analyzed through the results of tests made up of students with the determination of seven categories, namely: the theme of the poem, the mandate, the content of the poem, the tone, the use of figurative language, diction, and concrete words. Assessment is done by determining the weight of each category to reach a value of 100. Furthermore, the behavior data were analyzed based on the results of the second cycle. Results cycles (1) indicates that the application of a constructivist approach by teachers in the classroom does not achieve effective results because of the problems of teaching teachers who have not been able to accommodate the learning resources well so that students are not motivated and enthusiastic about learning, especially learning to write poetry. Therefore, the result of reflection cycle (1) became the basis for the preparation of the cycle (2). Results cycles (2) shows that the significance of learning, increased motivation, creativity, level of imagination and creativity of the students can be more effective by increasing the professionalism of teachers in teaching junior high school students SMP Kartika XX_2 Makassar with a constructivist approach in the classroom. The results of the cycle (2) can be proved by the teacher of the test results of students by the teacher wrote a poem after poem writing activities implemented. Of the 35 students, 28 of whom were categorized been able to produce poems. It is based on seven assessment categories selected researchers as a condition of the pen. Ke-28 such students reach the weight value of 75 upwards. Finally, these results indicate that the constructivist approach effectively applied to improve students' ability to write poetry class VIII SMP Negari 4 Kotabaru.